Beyond Traditional Audits: The Implications of Information Technology on Auditing - Shaikh, Humaiz; Uzair Jokhio, Mohammad; Ahmed Maher, Zulfikar; Chandio, Shahmurad; Manirajah, Mirza; Abdullah, Bin; Raza, Ali; Salam, Shah; Shah, Asadullah (International Journal of Engineering and Technology, 2018)
This paper examines the manner in which audits would be conducted in the future and how technology has transformed and impacted the business processes of public, private sector entities and various organisations and the guidelines which need to be followed to ensure compliance with applicable laws and regulations. The tranperancy of financial statements is of paramount interest to shareholders and other significant stakeholders. This necessities that the financial statements are audited to acquire a certain level of confidence over the integrity of numbers and the validity of business rationale which thereby arises a need for auditor to be well equipped with all the tools and system essentials in carrying out an effective and efficient audit. Information Technology can act as an impediment or stimulant towards the achievement of the above discussed objective. Various organizations use automation tools and ERP applications which have become a vital cog in their internel control environment. Understanding by auditor of these automated controls is necessary to ensure that the they are Â well equipped with the requisite skills and have knowledge of all technological tweaks that would be required in the audit process of a complex structured entity. The primary function which can be performed by generalized audit software include customizing data in numrous ways to serve the distinct purpose. The audit teams obtain insights into latest developments and plan their procedures accordingly keeping in view the applicable professional standards. Â  Â